Odpowiedzi

2010-03-23T13:46:40+01:00
A) 12y - (y+5) = 10y - 1
12y-y-5=10-1
12y-y-10y=1+5
y=6

b) 2 (u-5) + 15 = 3(u-4) + 10
2u-10+15=3u-2+10
2u-3u=-12+10-10+15
-u=3 :(-1)
u=-3
1 1 1
2010-03-23T13:48:05+01:00
A) 12y - (y+5) = 10y - 1
12y-y-5=10y-1
11y-10y=5-1
y=4
b) 2 (u-5) + 15 = 3(u-4) + 10
2u-10+15=3u-12+10
2u-3u=10-15-12+10
-u=-7/(-1)
u=7
2 5 2
2010-03-23T13:48:22+01:00
A) 12y-(y+5)=10y-1 ; 12y-y-5=10y-1 ; 11y-10y=-1+5 ; y=4 ; b)2(u-5)+15=3(u-4)+10 ;2u-10=3u-12+10 ; 2u-3u=-12+10+10 ;-u=8 ;u=-8